Book Review "Room" - Putri, Fanny Alisya (Linguistika Kultura, 2023)
We live in a popular culture where depression has become a thing that is almost sought after. Thus, we all struggle with an obstacle of life: going through mundane lives with empty souls in a hopeless, dark place. Speaking of desperate places, Room (2010), a novel written by Emma Donoghue, attempts to answer how captivating life in a world of pressure provides no alternative options but committing suicide or escaping. Emma Donoghue, an Irish-Canadian author, was born on 24 October 1969, living in an English society where mental health problems such as depression carried public attention.